Efek Sitotoksik Ekstrak Metanol Akar Tumbuhan Purwoceng (Pimpinella Alpina) Terhadap Sel Kanker Payudara ( MCF-7 Breast Cancer Cells) - Permana, Dharma; Usman, Herman (Lembaga Penelitian Universitas YARSI, 2013)
Background. Purwoceng (Pimpinella alpina) is one of the plants which has a property as a traditional medicine and the roots of this plant has been known as a sexual desire arousing (aphrodisiac). Epoxypseudoisoeugenol -2-methyl butyrate (EPB), a phenylpropranoid isolated from Pimpinella corymbosa inhibited the proliferation of both MCF-7 and BT-549 cells. Objective. This study aims to investigate of the cytotoxic effect of methanolic extracts from the roots of Pimpinella alpina on MCF-7 cells line in vitro. Methods. The In vitro cytotoxicity of methanolic extracts of the roots of Pimpinella alpina was studied using variousconcentrations (0.1, 1, 10 and 100 ?g/ml) by MTT viability assay. The MTT [3-(4,5-dimethylthiazol-2-y1)-2,5- diphenyl–tetrazolium bromide] salt will be induced to its coloured formazan by the action of mitochondrial dehydrogenes. The MTT formazan product is dissolved in DMSO and the amount is estimated by measuring absorbance at 550 nm using an ELISA plate reader. The IC50 values (concentration of a extracts that produces 50% reduction in the absorbance compared with untreated controls) are determined from the dose-response curves. Results. The in vitro screening of the methanolic extracts showed strong cytotoxic activity on MCF-7 Breast Cancer cells. The significant decrease in cell viability was observed for 100 ?g/ml and the IC50 value is 22.98 ?g/ml. Conclusion. The results indicated that methanolic extract of the roots of Pimpinella alpina has a potential cytotoxicity activity on MCF-7 Breast Cancer cells and considered to be a particularly valuable source of cytotoxic substances.